Association of indexes of added agro-stockbreeding value and value of animal production in São Paulo, Brazil - de Oliveira, Paulo André; Rodrigues, Sergio Augusto [UNESP]; Padovani, Carlos Roberto [UNESP]; Cervi, Ricardo Ghantous [UNESP] (Centro Universitario de Maringa, 2022)
Agricultural and stockbreeding added value and the value of agricultural and stockbreeding production reveal an association which has not been proportional over time. The importance of the association lies in different areas such as taxes and follow-up of the sector´s economic activity. Current research measures simultaneously the association between the set of indexes of the agricultural and stockbreeding added value and the value of agricultural and stockbreeding production of animal-derived products in regions of the state of São Paulo, Brazil. A better understanding of the dynamics of production value of the main products derived from animals in indexes related to the added value of agriculture and stockbreeding. The units under analysis were each of the forty administrative regions of the Rural Development Offices (EDR) of the state of São Paulo in the years 2007 and 2016, with 13 indexes in two groups. Association between groups was made by canonical co-relationship. The participation of animal-derived products, bovine and participation of milk in animal products, may be underscored due to their economic importance and to the antagonist behavior with regard to other production variables. The above may be explained by the complementarity of animal production in areas with slight trends for agricultural production.
Associação de indicadores do valor adicionado agropecuário e o valor da produção animal paulista
Keywords: Multivariate analysis; Profit; Regions